Desain Diskusi Matematika yang Menguntungkan bagi Siswa - Anwar Rifa'i (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The quality of discussion in the classroom is one of the important factors that determine the mathematics learning outcome. Mathematics discussion has been proven can help students to understand mathematics concepts (Goos, 1995; Lee, 2006). A good mathematical discussion will provide an opportunity for students to exchange ideas, develop communication skills, thinking skills, understanding of the concept and encourage the emergence of new ideas. In the other hand, there is other evidence which stated that the mathematics discussion does not always bring a positive impact on learning outcomes for mathematics (Shouse, 2001). Because of that, it is importat to know about the benefical mathematics discussion design for students. This article tries to present a favorable mathematics discussion design for students. 5 Best Practices for orchestrating Productive Discussions by NCTM became one of the foundations of this mathematics discussion design. Based on studies conducted, the mathenatics discussion design that is beneficial to students described in several parts: the preparation of the discussion, the role of teacher and also the role of students in mathematics discussion.